Expression signatures of DNA repair genes correlate with survival prognosis of astrocytoma patients. Issue 4 (April 2017) - de Sousa, Juliana Ferreira; Torrieri, Raul; Serafim, Rodolfo Bortolozo; Di Cristofaro, Luis Fernando Macedo; Escanfella, Fábio Dalbon; Ribeiro, Rodrigo; Zanette, Dalila Lucíola; Paçó-Larson, Maria Luisa; da Silva, Wilson Araujo; Tirapelli, Daniela Pretti da Cunha; Neder, Luciano; Carlotti, Carlos Gilberto; et al.
Astrocytomas are the most common primary brain tumors. They are very resistant to therapies and usually progress rapidly to high-grade lesions. Here, we investigated the potential role of DNA repair genes in astrocytoma progression and resistance. To this aim, we performed a polymerase chain reaction array-based analysis focused on DNA repair genes and searched for correlations between expression patters and survival prognoses. We found 19 genes significantly altered. Combining these genes in all possible arrangements, we found 421 expression signatures strongly associated with poor survival. Importantly, five genes (DDB2, EXO1, NEIL3, BRCA2, and BRIP1) were independently correlated with worse prognoses, revealing single-gene signatures. Moreover, silencing of EXO1, which is remarkably overexpressed, promoted faster restoration of double-strand breaks, while NEIL3 knockdown, also highly overexpressed, caused an increment in DNA damage and cell death after irradiation of glioblastoma cells. These results disclose the importance of DNA repair pathways for the maintenance of genomic stability of high-grade astrocytomas and suggest that EXO1 and NEIL3 overexpression confers more efficiency for double-strand break repair and resistance to reactive oxygen species, respectively. Thereby, we highlight these two genes as potentially related with tumor aggressiveness and promising candidates as novel therapeutic targets.